Socio-economic impact of COVID-19 pandemic and its coping measures in a rural area of central Kerala - Vijayan, Sajna M.; Abraham, Ruth; Vanlalhriatpuii, Emmanuelle (International Journal Of Community Medicine And Public Health, 2022)
Background: The COVID-19 pandemic is certainly considered one among the largest human disaster in the current decade, causing simultaneous health and socioeconomic suffering. This study was conducted to study the socioeconomic impact of COVID-19 pandemic at the household level and the coping measures among adults in a rural area. Methods: A cross-sectional study was conducted in a rural area of Thrissur district for a period of eight months. Cluster sampling was done. Among the total subcentres in a rural primary health centre (PHC), one subcentre was selected using lottery method. The consecutive houses were included till the calculated sample size was obtained. After establishing a rapport with the subject, data was collected using a semi-structured interview schedule from the participant using questions in local language. Results: Mean age was 47.6±13.7 years. The common social impacts due to the pandemic were loss of job (53.8%), difficulty in finding jobs (47.1%) difficulty due to inability to travel (37%), skipping of at least one of the meals (27.5%), difficulty in travelling back to permanent home (20.7%), difficulty in getting health services (14.4%). The major economic impacts were losing your wage due to lockdown (74%) and difficulty in repaying loans (63%). The main coping measure was government’s public distribution system 72.3%. Conclusions: There were social issues and economic crisis due to COVID-19 pandemic and its lock down measures among the population. Both government and non-governmental sectors should understand the magnitude of the problem and should find the ways to tackle the situation.